How do drugs affect the skeleton? implications for forensic anthropology - Márquez-Grant, Nicholas; Baldini, Elisa; Jeynes, Victoria; Biehler-Gomez, Lucie; Aoukhiyad, Layla; Passalacqua, Nicholas V.; Giordano, Gaia; Di Candia, Domenico; Cattaneo, Cristina (MDPI, 2022)
Forensic anthropologists rely on a number of parameters when analyzing human skeletal remains to assist in the identification of the deceased, predominantly age-at-death, sex, stature, ancestry or population affinity, and any unique identifying features. During the examination of human remains, it is important to be aware that the skeletal features considered when applying anthropological methods may be influenced and modified by a number of factors, and particular to this article, prescription drugs (including medical and non-medical use) and other commonly used drugs. In view of this, this paper aims to review the medical, clinical and pharmacological literature to enable an assessment of those drug groups that as side effects have the potential to have an adverse effect on the skeleton, and explore whether or not they can influence the estimation of age-at-death, sex and other indicators of the biological profile. Moreover, it may be that the observation of certain alterations or inconsistencies in the skeleton may relate to the use of drugs or medication, and this in turn may help narrow down the list of missing persons to which a set of human remains could belong. The information gathered from the clinical and medical literature has been extracted with a forensic anthropological perspective and provides an awareness on how several drugs, such as opioids, cocaine, corticosteroids, non-steroidal anti-inflammatory drugs, alcohol, tobacco and others have notable effects on bone. Through different mechanisms, drugs can alter bone mineral density, causing osteopenia, osteoporosis, increase the risk of fractures, osteonecrosis, and oral changes. Not much has been written on the influence of drugs on the skeleton from the forensic anthropological practitioner perspective; and this review, in spite of its limitations and the requirement of further research, aims to investigate the current knowledge of the possible effects of both prescription and recreational drugs on bones, contributing to providing a better awareness in forensic anthropological practice and assisting in the identification process of the deceased.
Keywords: forensic anthropology; medication; drugs of abuse; biological profile; human identification